Nasopharyngeal carcinoma detection by tissue smears using surface-enhanced Raman spectroscopy. Issue 1 (2nd January 2017) - Xu, Zhihong; Ge, Xiaosong; Huang, Wei; Lin, Duo; Wu, Shanshan; Lin, Xueliang; Wu, Qiong; Sun, Liqing
ABSTRACT: Nasopharyngeal carcinoma is one of the most common malignant neoplasms in head and neck. In this work, surface-enhanced Raman spectroscopy technique was used to study the molecular differences between cancerous and noncancerous smear samples which were obtained after clinical biopsy by smearing the tissue on the slides. Principal component analysis combined with linear discriminant analysis provided a sensitivity of 79.4% and a specificity of 81.8% for differentiation between cancerous and noncancerous nasopharyngeal tissue smears. This work provides a good basis for the methodology of nasopharyngeal tissue smear based on surface-enhanced Raman spectroscopy technique and is worth further studying.